Viability RT-qPCR to Distinguish Between HEV and HAV With Intact and Altered Capsids - Randazzo, Walter; Vasquez-García, Andrea; Aznar, Rosa; Sánchez, Gloria (Frontiers in Microbiology, 2018)
The hepatitis E virus (HEV) is an emerging pathogen showing a considerable increase in the number of reported cases in Europe mainly related to the ingestion of contaminated food. As with other relevant viral foodborne pathogens, real-time reverse transcriptase polymerase chain reaction (RT-qPCR) is the gold standard for HEV detection in clinical, food, and environmental samples, but these procedures cannot discriminate between inactivated and potentially infectious viruses. Thus, the aim of this study was to develop a viability PCR method to discriminate between native, heat-, and high-pressure processing (HPP)- treated HEV using the hepatitis A virus (HAV) as a cultivable surrogate. To this end, different concentrations of viability markers (PMAxx and platinum chloride, PtCl4) were screened firstly on purified viral RNA using different RT-qPCR assays. Reductions of HEV RNA signals of >17.5, >15.0, and >15.5 quantification cycles (Cq) were reported for PtCl4 and 1.6, 2.9, and 8.4 Cq for PMAxx, clearly indicating a better performance of PtCl4 than PMAxx irrespective of the RT-qPCR assays used. The most efficient viability pretreatment (500 µM PtCl4 incubated at 5°C for 30 min) was then assessed on native, heat-, and HPP-treated HEV suspension. The optimized viability RT-qPCR discriminated successfully between native, heat-, and HPP- treated HEV, to different extents depending on the experimental conditions. In particular, approximately 2-log reduction was reported by PtCl4-RT-qPCR at both 72 and 95°C compared to the control. Additionally, both viability pretreatments were tested for HPP-treated HAV without success, while PtCl4-RT-qPCR completely eliminated (>5.6-log reduction) the RT-qPCR signals of HPP-treated HEV. Although this viability procedure may still overestimate infectivity, the PtCl4 pretreatment represents progress to better interpreting the quantification of intact HEV, and it could be included in molecular procedures used to quantify enteric viruses in food and environmental samples.